Body mass index has an impact on preoperative symptoms but not clinical outcome in acute cauda equina syndrome - Vicki M. Butenschoen (Nature Portfolio, 2021)
Abstract Cauda equina syndrome (CES) presents a surgical emergency with treatment required within 48 h. Symptoms include reduced saddle sensation, micturition difficulties, and/or anal sphincter impairment. Controversy exists regarding the effect on and coincidence of overweight with CES. We performed a retrospective case–control study of all patients treated surgically for acute complete and incomplete CES in our neurosurgical department from 2009 to 2020, focusing on the preoperative BMI and postoperative neurological outcome. In addition, we performed a comprehensive literature review. Fifty patients with CES were included, of whom 96% suffered from a decompensated lumbar spinal stenosis or disc prolapse between the L4/5 and L5/S1 levels. Our cohort population was overweight but not obese: mean BMI was 27.5 kg/m2, compared with 27.6 kg/m2 in patients with degenerative spine surgery. BMI did not significantly influence the postoperative outcome, but it did affect preoperative symptoms and surgery duration. Symptom duration significantly differed depending on the underlying cause for CES. The literature review revealed sparse evidence, with only four clinical case series presenting contradictory results. We provide a comprehensive literature review on the current evidence regarding CES and obesity and conclude that we did not observe an association between obesity and CES occurrence. Patients with CES and other degenerative spinal pathologies belong to an overweight but not obese population. Body Mass Index has an impact on preoperative symptoms but not clinical outcome in acute CES.